ANALISIS PERAN PEMERINTAH KOTA KUPANG DALAM MEWUJUDKAN KOTA KUPANG MENJADI KOTA LAYAK ANAK - Silviana Dewi, Nataly; Ngau Lobo, Ferdinandus; Morison Deze, Januarius (Gapenas Publisher, 2024)
In this article, we analyze the role of the Kupang City Government in making Kupang City a Child Friendly City (KLA). Children have the right to grow and develop in a safe and healthy environment, so the government's responsibility is very important in ensuring that they provide them with their rights. This research uses empirical juridical methods, combining literature studies and field data. The results show that the government must collaborate with society, non-governmental organizations, and the private sector to create responsive policies. Some of the challenges faced include social, economic and cultural conditions that influence policy implementation. This article recommends a participatory approach in formulating policies, identifying children's needs, as well as concrete development programs. With the right steps, it is hoped that Kupang City can become an example for other regions in fulfilling children's rights and protecting children effectively. Through joint commitment, it is hoped that KLA can be realized well, providing benefits for the future of children in Kupang City.